Aphasia communication groups in Cyprus: The Aphasia Communication Team (TACT) - Charalambous, Marina; Kambanaros, Maria (My University, 2020)
Background And Aims: Between 1,200 – 1,400 people in Cyprus experience a stroke every year. Aphasia, a communication breakdown because of stroke, affects 30% of stroke survivors. Aphasia impacts comprehension and production of spoken and/or written language and is linked to poorer functional recovery, activities of daily living, depression & social isolation after stroke. The Aphasia Communication Team – TACT aims to provide stroke survivors support for learning and communication opportunities to promote living well with aphasia. Methods: The Cyprus Stroke Association recruits stroke survivors and TACT is held at the premises of the Rehabilitation Clinic of the Cyprus University of Technology. Groups consist of six stroke survivors with chronic aphasia and six communication buddies. Group members are assessed on psychometric measures based on the I-PRAISE protocol. Group members share experiences by using technology/tablets and total communication approach. The main topics of discussion are stroke and aphasia, linking the information to members own experiences and discussing living with aphasia. Results: Outcomes consist of variations in measures of functional communication, overall severity of language impairment from baseline, self-rating and quality of life after stroke. Data gathered are digitalized for each group member based of the RELEASE protocol. Conclusions: The use of the communication buddy system, the involvement of the total communication approach, the systematic assessment and the collection of individual patient data will enable us to measure the effectiveness and efficacy of group therapy interventions for stroke survivors with chronic aphasia in terms of use of functional communication, social inclusion and quality of life.
Keywords: Stroke survivors; Learning; Communication opportunities; Aphasia